Resting-state functional connectivity in a non-human primate model of cortical ischemic stroke in area F1 - Jiang, Shenzhong; Yang, Chengxian; Wang, Renzhi; Bao, Xinjie (Magnetic resonance imaging, 2023)
The application of functional MRI to non-human primates after stroke has not yet been undertaken. This is the first study to explore the functional connectivity changes in non-human primate models during acute stages after stroke onset. Nineteen healthy male cynomolgus monkeys (4–5 years) were used in this study. The photothrombosis model was employed to induce focal ischemic stroke in F1 area in the monkey's left hemisphere. T1-weighted structural images and resting-state functional magnetic resonance imaging (rs-fMRI) of all subjects were obtained using a 3.0 Tesla MRI system on the third day following stroke. Based on the D99 atlas, the structural and functional changes of bilateral F1 areas in monkeys were analyzed using region of interest (ROI)-based functional connectivity (FC). The bilateral F1 areas were selected as the seed regions due to their crucial role in motor control and their potential to unveil the comprehensive functional reorganization of the motor system at a whole-brain level following stroke. Ischemic lesions were observed after the stroke, with larger lesion volumes associated with poorer neurological dysfunction. Compared with baseline condition, left area F1 demonstrated decreased FC with the left cerebellum, left ventral pons and left 5_(PEa). When the ROI was located in the right area F1, ischemic monkeys showed decreased FC in left ventral pons, left cerebellum, left primary visual cortex and left 5_(PEa), accompanied by increased FC in the right orbitofrontal cortex. Importantly, the degree of altered FC between left area F1 and left cerebellum was associated with upper limb tone. These results provide valuable insights into the early-stage functional connectivity changes in the F1 areas of monkeys under ischemic conditions, highlighting the potential involvement of specific brain regions in the pathophysiology of ischemic injury.